Characteristics of pulmonary tuberculosis patients in Moses Kotane region North West Province, South Africa - Jean Louis Yoko; John Tumbo; Benjamin A Mills; Cila Dominic Kabongo (South African Family Practice)
Aim: To determine the characteristics of patients with pulmonary tuberculosis registered in primary health care facilities in Moses Kotane region North West Province.